Produção de etanol a partir da fração hemicelulósica do bagaço de cana usando glicose isomerase coimobilizada com Saccharomyces cerevisiae - Silva, Claudia Ramos da (Universidade Federal de São Carlos, 2014)
Glucose isomerase (GI) was covalently immobilized and co-immobilized with baker yeast in calcium alginate beads for ethanol production by simultaneous isomerization and fermentation of xylose or hemicellulose hydrolysate from bagasse. GI was covalently immobilized on glutaraldehyde-chitosan and high protein loads were immobilized (30-68 support mg.g-1). High immobilization yields (100%) and activity recovery (90%) were achieved. Under typical operation conditions of simultaneous isomerization and fermentation (pH 5, 35°C, medium with nutrients and ethanol concentrations up to 70g.L-1) the derivative remained 90% of initial activity after 120 hours. Calcium carbonate was used to maintain the pH in isomerization/fermentation medium higher than 5.0, ensuring high conversion of xylose at 32- 35°C. Accordingly, concentrations of enzyme and yeast in the reactor of 60-120.103UI.L-1 and 50g.L-1, respectively, resulted in better yields and selectivity for ethanol batch production. After consumption of ~ 65g.L-1 of xylose in about 12 hours, 21g.L-1 of ethanol and 14g.L-1 of xylitol was produced. In a medium without calcium carbonate, partial sugar conversion was observed due to the reduction of pH medium, which decreased up to 4.7, causing the inactivation of GI. The treatment of sugarcane bagasse with diluted acid resulted in hydrolysate with 61.0g. L-1 of xylose, 7.3g.L-1 of arabinose, 7.2g.L-1 of glucose, 10.4g.L-1 of acetic acid, 0.53g.L-1 of furfural, 0.06g.L-1 of hydroxymethylfurfural and 4.3g.L-1 of lignin derivatives. Baker yeast was able to produce ethanol from non-detoxified liquid hydrolysate as efficiently as pure xylose medium. Simultaneous isomerization and fermentation using non-detoxified hydrolysate led to 23 g.L-1 ethanol, yield of 0.34g.g-1 and a productivity of 1.8g.L-1.h-1. Continuous process was conducted for 7 days. The operation for longer periods of time will be possible with pH control and microbial contamination prevention.
Keywords: Fermentaçã; Etanol; Bagaço de cana; Hemicelulose; S. cerevisiae; ENGENHARIAS::ENGENHARIA QUIMICA